The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.3390/fermentation9121026
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into the Biosynthesis of Succinic Acid by Actinobacillus succinogenes with the Help of Its Engineered Strains

Chunmei Chen,
Pu Zheng

Abstract: Succinic acid (SA), a C4 tricarboxylic acid cycle intermediate, is used as raw material for bulk chemicals and specialty chemicals, such as tetrahydrofuran and 1,4-butanediol, as well as also being used to synthesize the biodegradable biopolymers PBS (polymer poly (butylene succinate)). Actinobacillus succinogenes, which is facultative anaerobic and gram-negative, is one of the most promising natural SA-producing organisms, but genetic engineering of A. succinogenes is rare so far. In this study, a series of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…After five fermentation cycles with a total time of 72 h, 147.6 g/L of glucose was metabolized, leading to a SA concentration of 107 g/L. In the most recent study, Chen and Zheng altered several genes in Actinobacillus strain which were anticipated to play a crucial role in the microbial growth and SA production using pLGZ922 expression vector and a cytosine base editor (CBE) based on CRISPR/Cas9 [ 39 ].Their study revealed that when two of the genes, namely, pyc (pyruvate carboxylase) and pepc (phosphoenolpyruvate carboxylase) from Corynebacterium acetoacidophilum , which were instrumental in CO 2 fixation were individually over-expressed in A. succinogenes , the SA titers increased from 52.35 to 55.66 and 59.47 g/L, respectively. Despite a delayed growth, the SA yields were enhanced from 0.70 g/g to 0.82 and 0.79 g/g, respectively.…”
Section: Native Producers Of Samentioning
confidence: 99%
See 1 more Smart Citation
“…After five fermentation cycles with a total time of 72 h, 147.6 g/L of glucose was metabolized, leading to a SA concentration of 107 g/L. In the most recent study, Chen and Zheng altered several genes in Actinobacillus strain which were anticipated to play a crucial role in the microbial growth and SA production using pLGZ922 expression vector and a cytosine base editor (CBE) based on CRISPR/Cas9 [ 39 ].Their study revealed that when two of the genes, namely, pyc (pyruvate carboxylase) and pepc (phosphoenolpyruvate carboxylase) from Corynebacterium acetoacidophilum , which were instrumental in CO 2 fixation were individually over-expressed in A. succinogenes , the SA titers increased from 52.35 to 55.66 and 59.47 g/L, respectively. Despite a delayed growth, the SA yields were enhanced from 0.70 g/g to 0.82 and 0.79 g/g, respectively.…”
Section: Native Producers Of Samentioning
confidence: 99%
“…It is the first study wherein data mining of certain sugar and SA transporters was done. When two genes that encoded for two SA exporters, namely, Asuc_0716 and Asuc_0715, were individually knocked out, it had a prominent and deleterious effect on both cell homeostasis and SA biosynthesis [ 39 ]. In the same year Chen et al, developed an efficient, fast and precise gene manipulation toolkit for editing the genes of Actinobacillus by developing series of specific base editors (BE’s) by fusing Cas nuclease and cytidine/adenine deaminase [ 40 ].…”
Section: Native Producers Of Samentioning
confidence: 99%